Two new species of genus Cephalaria from Anatolia (Türkiye) - Göktürk, Ramazan Süleyman; Hamzaoğlu, Ergi̇n; Yildirim, Hasan; Kaya, Ergun; Galatali, Seli̇n; Çi̇çek, Sedat; Özdöl, Tuğkan; Özdemi̇r, Rifat (Phytotaxa, 2025)
Cephalaria cameliensis (Caprifoliaceae) and C. dumanii are described from Anatolia as two new taxa of Türkiye. Diagnostic morphological and molecular characters from closely similar taxa are discussed. Taxonomic with the help of molecular techniques, ecology, and conservation status for these two new species are given even through geographical distribution. Twenty-three ISSR primers were tested in addition to morphological features in determining the taxa of Cephalaria cameliensis, C. dirmilensis, C. saldaensis, and C. lycica, and six of them showed reproducible and polymorphic band profiles. The images of PCR products obtained with these six primers were examined on agarose gel, a total of 93 band profiles ranging between 250 bp and 3100 bp were determined. In the dendrogram analyses performed with UPGMA based on Jaccard similarity values, it was molecularly supported that the four morphologically separated taxa also differ at the species level. Finally, C. dumanii, identified in the current study as a new species belonging to a distinct Cephalaria group, was also molecularly compared with C. paphlagonica and C. kutahyaensis from the same group. Four ISSR primers yielded 53 polymorphic band profiles ranging between 110 bp and 2800 bp. Molecular data supported that C. dumanii is distinctly separated from the other two taxa in this group.